Strategy of Handover in Mobile Relay Group in LTE-Networks - Al Hakam Ayad Salih (Zien Journals, 2022)
The small cell technology is giving rise to a new field known as mobile cell, which is expected to dominate the networks of the future. Mobile relay is an important component of mobile cells because it enables mobile user equipment (UE) to keep their network connectivity with a high quality of experience to the microcell base station even while they are moving at high speeds in their vehicles. The use of group handover is a great option for managing the large number of handovers that are caused by transferring user equipment (UEs) within the mobile cell. In this research, we present a group handover technique that is both effective and efficient for mobile cells operating in LTE-Advanced systems. Using the group handover approach that has been proposed, a mobile relay node (MRN) that is attached to a high-speed train will transfer all of the communication that is relevant to UEs from the source donor eNB (DeNB) to the target DeNB. moreover, in contrast to the majority of previous works, which make use of a fixed relay design, this work makes use of a mobile relay architecture. The proposed group handover approach was implemented on the mobile cell, which resulted in a significant reduction in numbers of handovers and the probability of calls getting dropped throughout the system.
Keywords: Handover; High-speed railway; LTE; MRN